A NanoLuc luciferase‐based assay enabling the real‐time analysis of protein secretion and injection by bacterial type III secretion systems. Issue 6 (4th March 2020) - Westerhausen, Sibel; Nowak, Melanie; Torres‐Vargas, Claudia E.; Bilitewski, Ursula; Bohn, Erwin; Grin, Iwan; Wagner, Samuel
Abstract: The elucidation of the molecular mechanisms of secretion through bacterial protein secretion systems is impeded by a shortage of assays to quantitatively assess secretion kinetics. Also the analysis of the biological role of these secretion systems as well as the identification of inhibitors targeting these systems would greatly benefit from the availability of a simple, quick and quantitative assay to monitor principle secretion and injection into host cells. Here, we present a versatile solution to this need, utilizing the small and very bright NanoLuc luciferase to assess the function of the type III secretion system encoded by Salmonella pathogenicity island 1. Type III secretion substrate–NanoLuc fusions are readily secreted into the culture supernatant, where they can be quantified by luminometry after removal of bacteria. The NanoLuc‐based secretion assay features a very high signal‐to‐noise ratio and sensitivity down to the nanolitre scale. The assay enables monitoring of secretion kinetics and is adaptable to a high throughput screening format in 384‐well microplates. We further developed a split NanoLuc‐based assay that enables the real‐time monitoring of type III secretion‐dependent injection of effector–HiBiT fusions into host cells stably expressing the complementing NanoLuc–LgBiT. Abstract : We developed a luciferase‐based assay to enable the simple, quick, quantitative and high‐throughput compatible assessment of secretion and injection through virulence‐associated type III secretion systems. The assay allows detection of minute amounts of secreted substrate proteins either in the supernatant of the bacterial culture or within eukaryotic host cells.